Diabetes Self-Management Practices among Diabetic Patients Attending Chitwan Medical College Teaching Hospital - Ghimire, Harish Chandra; Ojha, Ojashvi (Nepal Journal of Health Sciences, 2023)
Introduction: Diabetes is a new health issue that affects many people around the world. The majority of the diabetic population lives in low-and middle-income countries. Diabetes has badly affected individuals, families, and countries. This problem can be minimized and managed through effective self-management practices.Objective: The present study aims to identify the level of self-management practices among type 2 diabetes mellitus patients.Methods: A descriptive and analytical cross-sectional study design was used to assess diabetes self-management practices. A standard ‘Summary of Diabetes Self-Care Activity’ tool was adopted with few modifications after pretesting. This study was carried out among 191 samples with diabetes type-2 patients attending the outpatient department of Chitwan Medical College Teaching Hospital. The non-probability consecutive sampling method was adopted for data collection. Ethical principles were addressed during the study.Results: Among the total participants, 51.8% had unsatisfactory diabetes self-management practices. Age, education, place of residence, religion, occupation, family history, comorbidity, duration of diagnosis, alcohol drinking, and smoking were associated with diabetes self-management practice. There were 55.5% male participants. The majority, 42.4% belonged to the age group 60 and above. The minimum age was 30, the maximum age was 94, and the mean age was 56.9 years. The majority (77%) of participants were literate.Conclusions: This study revealed an unsatisfactory level of diabetes self-management practices. This finding implies that diabetes self- management practice-related education programs should be created and implemented for people who are impacted, as well as for those who provide care at home.